The impact of the new World Symposium on Pulmonary Hypertension definition of pulmonary hypertension on the prevalence of pre-capillary pulmonary hypertension - Ümit Yaşar Sinan; Özge Çetinarslan; Alev Arat Özkan; Murat Kazım Ersanlı; Mehmet Serdar Küçükoğlu (KARE Publishing, 2019)
Objective: Since the first World Symposium on Pulmonary Hypertension (WSPH; Geneva, 1973), pulmonary hypertension (PH) has been defined as a mean pulmonary artery pressure (mPAP) ≥25 mm Hg measured at right heart catheterization (RHC) while at rest in the supine position. At the 6th WSPH congress (Nice, 2018), a new proposal was presented defining pre-capillary PH as mPAP >20 mm Hg, with pulmonary arterial wedge pressure (PAWP) <15 mm Hg, and pulmonary vascular resistance (PVR) >3 WU. The aim of this study was to investigate the impact of the new definition of PH on the number of pre-capillary PH patients. Methods: The results of RHC performed with various clinical indications between 2017 and 2018 were analyzed. The 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) and the 6th WSPH congress PH definitions were used to identify PH patients. Results: Fifty-eight RHC procedures were performed in our hospital in a 1-year period. Most were performed with a suspicion of PH (n=52). The remainder (n=6) were performed with indications of valvular heart disease or left heart disease. There were 40 females (69%) and 18 males (31%). The mean age was 53.3+-16.6 years. The RHC results revealed a mean PAP of 36.4+-16.4 mm Hg, PAWP of 12.6+-3.9 mm Hg, and PVR of 4.9+-4.4 WU. Forty-three of 58 patients (74.1%) were classified as pre-capillary PH according to the ESC/ERS PH guideline, whereas 50 of 58 patients (86.2%) had pre-capillary PH according to the new WSPH definition. Conclusion: The results of this study indicated that the impact of the new definition of PH on the number of pre-capillary PH patients identified was greater than the predicted <10%.